2008
DOI: 10.1159/000139152
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Abnormalities among First-Degree Relatives of Children with Congenital Hypothyroidism: An Ultrasound Survey

Abstract: Background: Congenital hypothyroidism (CH) is caused by thyroid dysgenesis and dyshormonogenesis. Evidence suggests the presence of genetic factors in both types of pathogenesis. We investigated whether an increased incidence of thyroid abnormalities could be shown by ultrasonography among first-degree relatives of children with CH. Material and Methods: In this case-control study the presence of both developmental and non-developmental thyroid abnormalities was studied among first-degree relatives of CH patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
1
11
1
Order By: Relevance
“…The major objective of the study was to defi ne the prevalence of thyroid development and migration anomalies in fi rst-degree relatives of children with CH and TD. According to the literature, similar investigations were carried out by L é ger et al (15) , Adibi et al (30) , and Karakoc et al (29) . L é ger et al (15) demonstrated that the prevalence of asymptomatic TD among fi rst-degree relatives of children with CH in the French population was 7.9 % .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The major objective of the study was to defi ne the prevalence of thyroid development and migration anomalies in fi rst-degree relatives of children with CH and TD. According to the literature, similar investigations were carried out by L é ger et al (15) , Adibi et al (30) , and Karakoc et al (29) . L é ger et al (15) demonstrated that the prevalence of asymptomatic TD among fi rst-degree relatives of children with CH in the French population was 7.9 % .…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, investigations carried out in Iranian families by Adibi et al (30) demonstrate a similar prevalence of developmental thyroid disturbances in families of children with CH and TD. Asymptomatic disturbances of thyroid development were noted in 7.7 % of fi rst-degree relatives of children with CH resulting from agenesis, hemiagenesis, or thyroid ectopy.…”
Section: Discussionmentioning
confidence: 78%
“…Seventy-five percent of their reported thyroid developmental abnormalities were thyroid hemiagenesia, which is a rare form of TD, which can occur as a familial disorder, associated with any form of TD. [50] Most subjects with this abnormality may present with subclinical hypothyroidism. [51] Our observations, in accordance with the studies.…”
Section: Reviewmentioning
confidence: 99%
“…A hereditary component is further suggested by observations of an increased prevalence of occult developmental anomalies of the thyroid in asymptomatic first-degree relatives (Leger et al 2002, Adibi et al 2008, Karakoc et al 2008). However, it should be firmly kept in mind that monozygotic twins are generally discordant for TD (Perry et al 2002), arguing against simple Mendelian transmission (Deladoey et al 2007b, Castanet et al 2010.…”
Section: What Can We Learn From Patients?mentioning
confidence: 97%